2022
DOI: 10.3390/antiox11010117
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Paraptotic Cell Death in Breast Cancer Cells by a Novel Pyrazolo[3,4-h]quinoline Derivative through ROS Production and Endoplasmic Reticulum Stress

Abstract: Chemotherapy has been a standard intervention for a variety of cancers to impede tumor growth, mainly by inducing apoptosis. However, development of resistance to this regimen has led to a growing interest and demand for drugs targeting alternative cell death modes, such as paraptosis. Here, we designed and synthesized a novel derivative of a pyrazolo[3,4-h]quinoline scaffold (YRL1091), evaluated its cytotoxic effect, and elucidated the underlying molecular mechanisms of cell death in MDA-MB-231 and MCF-7 brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…We have here shown that ZA, a bisphosphonate safely used for osteoporosis, has a signi cant effect on the removal of PGCCs. It has recently been observed that concomitant use of this drug with cisplatin in breast, bladder, kidney, and lung cancer has increased the e cacy of treatment (34)(35)(36)(37). However, to date, no study has speci cally examined the effect of ZA on PGCCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have here shown that ZA, a bisphosphonate safely used for osteoporosis, has a signi cant effect on the removal of PGCCs. It has recently been observed that concomitant use of this drug with cisplatin in breast, bladder, kidney, and lung cancer has increased the e cacy of treatment (34)(35)(36)(37). However, to date, no study has speci cally examined the effect of ZA on PGCCs.…”
Section: Discussionmentioning
confidence: 99%
“…3). Although formation of vacuoles has previously been reported in response to cancer therapeutics [34] and some investigators have attributed them to therapy resistance [35], the content and function of these structures are yet elusive.…”
Section: Lipid Metabolism and Mitochondria Function Alter In Cisplati...mentioning
confidence: 99%
“…A549 lung cancer cells were cultured in RPMI containing 10% FBS and 1% antibiotic–antimycotic (composition given above). All cells were cultured and maintained in a humidified incubator at 37 °C with 5% CO 2 until 80–90% confluence and then trypsinized with 0.05%/0.5 mM trypsin−EDTA for experimental assays or a new passage culture, as previously described [ 48 , 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…The cells were washed and lysed with lysis buffer on ice. Electrophoresis and immunoblotting were performed according to procedures reported previously [ 49 , 50 ]. Briefly, lysates containing equal amounts of proteins were resolved by SDS-PAGE and transferred to nitrocellulose membranes at 100 V for 90 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation